Electrochemical Performance of BiF3‐BaF2 Solid Solution with Three Different Phases on a Fluoride Shuttle Battery System. Issue 16 (28th April 2020) - Konishi, Hiroaki; Minato, Taketoshi; Abe, Takeshi; Ogumi, Zempachi
Abstract: Solid solution of bismuth(III) fluoride (BiF3 ) and barium(II) fluoride (BaF2 ) with a variety of crystal structures was prepared, and their electrochemical performances were evaluated on a fluoride shuttle battery (FSB) system. BiF3 ‐BaF2 based solid solution (Bi1‐ x Ba x F3‐ x ( x =0) with orthorhombic phase, x =0.2 with hexagonal phase, and x =0.4 with cubic phase) were successfully obtained with the mechanical alloy method. The change from Bi1‐ x Ba x F3‐ x ( x =0) (orthorhombic) to x =0.2 (hexagonal) improved the initial reversible capacity and the capacity retention during cycling. The change from x =0.2 (hexagonal) to 0.4 (cubic) led to further improvement in capacity retention during cycling; however, the initial reversible capacity decreased due to the substitution of excess amount of barium that did not contribute to the redox reaction. For the BiF3 ‐based compound, controlling the crystal structure and substitution of inactive element affected the FSB performance. Abstract : The crystal structure of BiF3 ‐BaF2 solid solution can be controlled by the ratio of BiF3 and BaF2 . The battery performance of BiF3 ‐BaF2 solid solution was affected by the crystal structure. The BiF3 ‐BaF2 with a hexagonal phase exhibits higher reversible capacity than those with orthorhombic and cubic phases.